Generation of fast particle fluxes by finite amplitude electromagnetic waves in space plasma - Erokhin, N.S.; Zolnikova, N.N.; Grinevich, P.P.; Mikhailovskaya, L.A. (Вопросы атомной науки и техники, 2006)
The numerical calculations are performed to determine the regions of problem parameters in which the charged particles trapping and their following surfatron ultrarelativistic acceleration occur. It has been obtained the complicated structure of these region, in particular, the capture islands may exist with ultrarelativistic acceleration of charges. In the case of plasma without external magnetic field the charges acceleration by the packet of finite amplitude electrostatic waves is investigated. The optimal choice of waves parameters has been substantiated which are favourable ones for the charges acceleration and correspond to the main parametric resonance realization in the wave-particle interaction. The dependence of acceleration dynamics on the wave phases distribution is studied. Проведено численное моделирование для определения областей параметров задачи, в которых заряженные частицы захватываются и происходит их дальнейшее серфотронное релятивистское ускорение, в частности, могут существовать острова ультрарелятивистского ускорения зарядов. В случае плазмы без магнитного поля исследовано ускорение зарядов пакетом электростатических волн конечной амплитуды. Оптимальный выбор параметров волн, отвечающий приемлемым для ускорения зарядов условиям, соответствует реализации основного параметрического резонанса во взаимодействии волна-частица. Проведено чисельне моделювання для визначення областей параметрів задачі, в яких заряджені частинки захоплюються та відбувається їх подальше серфотронне релятивістське прискорення, зокрема, можуть існувати острови ультрарелятивістського прискорення зарядів. У випадку плазми без магнітного поля досліджено прискорення зарядів пакетом електростатичних хвиль скінченої амплітуди. Оптимальний вибір параметрів хвиль, що визначає прийнятні для прискорення зарядів умови, відповідає реалізації основного параметричного резонансу у взаємодії хвиля-частинка.